A study into the contingencies of process improvement methods. Issue 104 (February 2022) - Malinova, Monika; Gross, Steven; Mendling, Jan
Abstract: The design and improvement of business processes is of central importance for realizing benefits of information systems. A broad spectrum of methods has been proposed since the 1990s, which ranges into several dozen. It is unclear whether this large number trivially stems from copying and relabeling or whether there are substantial differences in these methods that can be tied to their applicability in different contexts or to the pursuit of different goals. Accordingly, we ask: Which activities do process improvement methods have in common, how do they differ, and why? In this paper, we approach these research questions using a multi-method design integrating techniques from systematic literature review, process mining, and statistical analysis. Our contributions are as follows. First, we provide a framework with 264 activities clustered in six stages that could be used for incrementally and radically improving processes. Second, we find that methods map to different configurations of the three dimensions described by the redesign orbit. Third, we uncover similarities and differences of the different methods contingent to the factors industry, objectives and whether a method is proposed or applied. Fourth, we observe three distinct clusters of method activities, which show that different strategies play a role when choosing a method for improvement. Our findings have important implications for the application of improvement methods in various improvement scenarios. Highlights: Process improvement methods evolve over time. Specific process improvement knowledge is implicitly available in the form of activities and sequences. The degree of innovativeness is evaluated by the type of method activities conducted for process improvement. Different strategies play a role when choosing a method for process improvement. There is an evident lack of process innovation methods.